Pygocephalid pancrustaceans from the late Carboniferous of Nova Scotia, Canada, with comments on the cuticular microstructures of Pygocephalamorpha - Laville, Thomas; Andréo, Antoine; Atkins, Jade B. (Atlantic Geoscience, 2026)
Pygocephalomorphs are fossil eumalacostracans with a shrimp to lobster-like morphology, known from the Late Devonian (Famennian) to the early Permian (Cisuralian; Artinskian). In the late Paleozoic, pygocephalamorphs formed an important component of marginal marine, brackish and freshwater communities. Several species, including species of Tealliocaris and Pygocephalus, have been described from the Carboniferous of Canada, in particular from the Pennsylvanian. A revision of Pygocephalus from the Carboniferous of Nova Scotia, Canada, is proposed based on original material described by Copeland and on undescribed material from the Joggins Fossil Cliffs UNESCO World Heritage Site. The presence of three taxa is confirmed: Pygocephalus cooperi, Pygocephalus cf. cooperi and Pygocephalus dubius. The pygocephalomorphs of Joggins Fossil Cliffs, and more generally Nova Scotia, were likely benthic walkers based on their leg morphology and the paleoichnological evidence. A comparison of the studied assemblages with previously known assemblages from the Mississippian of Canada shows a faunal turnover among these assemblages, which could reflect paleoenvironmental changes in Atlantic Canada during the Carboniferous and thus various ecological affinities among taxa. We also observed three types of microstructures on the shield of Pygocephalus dubius: canal-like pores, which are most probably organule canals, setal attachment site, and polygonal reticular ornamentation.